2015
DOI: 10.1093/ecco-jcc/jjv220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Biosimilar Infliximab CT-P13 Treatment in Inflammatory Bowel Diseases: A Prospective, Multicentre, Nationwide Cohort

Abstract: This prospective multicentre cohort shows that CT-P13 is safe and effective in the induction of clinical remission and response in both CD and UC. Patients with previous infliximab exposure exhibited decreased response rates and were more likely to develop allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 30 publications
8
131
0
5
Order By: Relevance
“…However, patients with previous infliximab exposure exhibited lower response rates and were more likely to develop allergic reactions [106].…”
Section: Biosimilars In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with previous infliximab exposure exhibited lower response rates and were more likely to develop allergic reactions [106].…”
Section: Biosimilars In Ibdmentioning
confidence: 99%
“…Multiple studies have shown that CT-P13 appears to have comparable efficacy and safety for patients requiring induction therapy and maintenance of remission in IBD [105,106]. Switching from the infliximab originator to its biosimilar was also shown to be safe in pediatric CD patients, and appeared to be as effective as the originator [107,108].…”
Section: Biosimilars In Ibdmentioning
confidence: 99%
“…Nevertheless, there is no evidence to support true interchangeability, which requires the safe and tolerable switch from originator to biosimilar and back again. Recent studies of infliximab biosimilars indicated efficacy and safety similar to the infliximab originator [95][96][97]. Importantly, antibodies to infliximab also recognize biosimilar infliximab [98].…”
Section: Future Directions Inflammatory Bowel Diseasementioning
confidence: 99%
“…Indeed, these studies could elucidate the controversial points regarding the efficacy and safety of the long-term use of this biosimilar drug (4) . A small number of cases of IBD patients treated with CT-P13 have been published to date (5,7,8,(10)(11)(12)17,21) . Moreover, it is also known that there is still no prospective head-to-head or non-inferiority randomized studies comparing CT-P13 with the reference IFX.…”
Section: Dear Sirmentioning
confidence: 99%